Molecular Targets for Chalcones in Antileishmanial Drug Discovery - de Santiago-Silva, Kaio M.; da Silva Gomes, Gabriel Felix; Perez, Carla Cristina; da Silva Lima, Camilo Henrique; de Lima Ferreira Bispo, Marcelle (Mini Reviews in Medicinal Chemistry, 2023)
Leishmaniases are infectious diseases caused by flagellated protozoan parasites belonging to the genus Leishmania that infect cells of the mononuclear phagocytic system. These parasites are transmitted to humans by biting an infected female sandfly belonging to the genera Phlebotomus in the Old World and Lutzomyia in the New World. Despite representing a major public health problem, the therapeutic options are old and have several disadvantages. Given this scenario, developing vaccines or drugs for oral administration is necessary. Therefore, integrating computational and experimental strategies into the studies on molecular targets essential for the survival and virulence of the parasite is fundamental in researching and developing new treatments for leishmaniasis. In the effort to develop new vaccines and drugs, molecular docking methods are widely used as they explore the adopted conformations of small molecules within the binding sites of macromolecular targets and estimate the free energy of target-ligand binding. Privileged structures have been widely used as an effective model in medicinal chemistry for drug discovery. Chalcones are a common simple scaffold found in many compounds of natural and synthetic origin, where studies demonstrate the great pharmacological potential in treating leishmaniasis. This review is based on scientific articles published in the last ten years on molecular docking of chalcone derivatives for essential molecular targets of Leishmania. Thus, this review emphasizes how versatile chalcone derivatives can be used in developing new inhibitors of important molecular targets involved in the survival, growth, cell differentiation, and infectivity of the parasites that cause leishmaniasis.
Keywords: structure-based drug design